TRADITIONAL SRI LANKAN MEDICINE INTERVENTION IN THE MANAGEMENT OF KNEE OSTEOARTHRITIS (JANU SANDIGATAVATA): CASE SERIES - Kamal Perera, *Pathirage; Chandra, N; Kumarasinghe, Nishantha (International Journal of Ayurveda and Pharma Research, 2018)
Background: Osteoarthritis (OA) of the knee is a degenerative disease, which significantly restricts the functions of the joint.  Janu Sandigatavata (JS) is considered to be the close equivalent in traditional medicine to OA in modern medicine. The aim of this case series was to report the effectiveness of Traditional Sri Lankan Medicine (TSM) on JS patients attend to National Ayurveda Teaching Hospital.Method: Reported cases (n=10) were at the age range of 45years to70 years and both female (n=8) and male (n=2) patients were diagnosed as having JS of the knee joints. Radiology (X-ray) reported by a radiologist confirmed that they were in Kellgren-Lawrence grade III or less. TSM treatments were given as regimens up to 86days. At the end point, external treatment of oleation and herbal immune enhancing drugs were further continued over 8 weeks. Visual analogue scale for pain, knee scores in Knee Society clinical Rating System (KSS) and Ayurveda clinical assessment criteria were used to evaluate the effects of treatment.Results: Reductions of visual analogue scale for pain was observed between baseline and the 86 days endpoint. Clinical assessment criteria and the KSS scores of pain, movement and stability were also improved up to good level and function score were improved up to excellent level. During the follow-up period, joint symptoms and signs and the knee scores were remaining unchanged.Conclusions: Study explored that substantial decrease in clinical parameters of OA in knee and improved patients’ quality of life by the intervention of the TSM.